2021
DOI: 10.1063/5.0032584
|View full text |Cite|
|
Sign up to set email alerts
|

Quantitative comparison of the magnetic proximity effect in Pt detected by XRMR and XMCD

Abstract: X-ray resonant magnetic reflectivity (XRMR) allows for the simultaneous measurement of structural, optical, and magneto-optic properties and depth profiles of a variety of thin film samples. However, a same-beamtime same-sample systematic quantitative comparison of the magnetic properties observed using XRMR and x-ray magnetic circular dichroism (XMCD) is still pending. Here, the XRMR results (Pt L 3 absorption edge) for the magnetic proximity effect in Pt deposited on the two different ferromagnetic materials… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…While this is an established effect in NiO, the size of the magneto-optic response stemming from NiO is remarkably large, in the same range as that of Fe 3 O 4 . However, conversion factors from β to μ B /atom can be of quite different size as recently observed for Pt and Pd [51,52]. The determination of this conversion factor for NiO is beyond the scope of this work and will be the focus of future research.…”
Section: Discussionmentioning
confidence: 66%
“…While this is an established effect in NiO, the size of the magneto-optic response stemming from NiO is remarkably large, in the same range as that of Fe 3 O 4 . However, conversion factors from β to μ B /atom can be of quite different size as recently observed for Pt and Pd [51,52]. The determination of this conversion factor for NiO is beyond the scope of this work and will be the focus of future research.…”
Section: Discussionmentioning
confidence: 66%
“…Our recent studies (Suturin et al, 2022) dedicated to the crystal structure of "-Fe 2 O 3 /GaN and carried out by means of HRTEM and reflection high-energy electron diffraction showed that there is a thin layer of magnetically soft �-Fe 2 O 3 at the film/substrate interface. Such an iron-oxide-on-nitride semiconductor system is a good example of a heterostructure for which separation of magnetic contributions of layers located at different depths (Jonnard et al, 2013;Moskaltsova et al, 2020;Graulich et al, 2021;Verna et al, 2021;Krieft et al, 2020) is of primary importance.…”
Section: Resultsmentioning
confidence: 99%
“…In [Pt/Co] N stacks, the Co thickness can modulate the magnetization through Co bulk effect and Pt/Co interface proximity effect 27 , change the interfacial spin transport behavior through spin memory loss and spin backflow 28 , and tune the spin/orbital currents through spin Hall effect (SHE) and orbital Hall effect (OHE) in Co and at the interfaces 29 , 30 , etc. Therefore, we sputtered Co-wedged samples of [Pt(1)/Co( t Co )] 5 on Si/SiO 2 substrates with t Co from 0.159 nm to 0.395 nm, and investigated the thickness-dependent magnetic and SOT properties.…”
Section: Resultsmentioning
confidence: 99%